2010
DOI: 10.1111/j.1365-4632.2010.04599.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DR alleles associated with skin warts induced by human papillomavirus infection

Abstract: This study follows the preponderant role of class II genes in the susceptibility or resistance to the development of skin warts caused by HPV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
(24 reference statements)
0
9
1
Order By: Relevance
“…Accompanying features such as growth retardation and poor oral hygiene of our patients might have been facilitating factors. According to other studies [ 10 , 11 ], the major histocompatibility complex might contribute to the HPV infection, however HLA typing of our patients revealed an HLA DQB1*0301phenotype. HPV infection has attracted a great deal of attention, not just because of the difficulty of managing oral warts but also because of the oncogenic potential of certain strains [ 12 ].…”
Section: Discussioncontrasting
confidence: 48%
“…Accompanying features such as growth retardation and poor oral hygiene of our patients might have been facilitating factors. According to other studies [ 10 , 11 ], the major histocompatibility complex might contribute to the HPV infection, however HLA typing of our patients revealed an HLA DQB1*0301phenotype. HPV infection has attracted a great deal of attention, not just because of the difficulty of managing oral warts but also because of the oncogenic potential of certain strains [ 12 ].…”
Section: Discussioncontrasting
confidence: 48%
“…HLA polymorphisms result in variations of peptide‐binding cleft, which may modify an adaptive immune response . The differences in binding affinities among HLA class II molecules were suggested to have a main role in the progression, persistence, and susceptibility to HPV infections . Studies in rabbits revealed that HLA class II antigens affect both regression and malignant transmission of cells infected with papillomavirus .…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested genetic variations in serological immune response to HPV infection. Only a few studies have recently focused on the association of HLA class II molecules and HPV‐induced mucocutaneous verrucous lesions because of their long‐lasting and therapy‐resistant properties . HLA DR3 and HLA DR9 alleles were considered to involve in persistence of the skin warts of Mexican patients, whereas HLA DR6 had a protective effect .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographical location could explain the effect of UVR in view of its capacity to impair host immunity [Termorshuizen et al, ], and make fair‐skinned individuals more susceptible to skin cancers and probably susceptible to different Beta‐species. Race and ethnicity could explain the role of immunogenetics i.e., certain HLA class II alleles have shown preponderance in the development of skin cancers associated with HPV [Garcia‐Corona et al, ] and hence particular allele types may have a predilection to the carcinogenic activity of certain Beta‐species. Socioeconomic factors including access to health services, livelihood, and lifestyle may predispose to particular Beta‐species infection.…”
Section: Discussionmentioning
confidence: 99%